SAN JOSE, A CITY IN PERPETUAL TRANSFORMATION. REFLECTIONS ON SPACE - Sánchez Lovell, Adriana (2013)
This article aims to introduce questions and proposals to approach the study of the transformations, contradictions and continuities present in the dynamics, relationships, meanings and everyday beliefs about San Jose city. We use space as our basic analytical unit, where we approach questions about changes in the social, relational, productive and labor sphere that arose in the last decades in the Costa Rican capital, and happen to gerate differentiated forms of appropriation and use of space that is increasingly characterized by segregation and discrimination.